Architecture in Institutional Management Systems using Odoo Enterprise Resource Planning at UIN Maulana Malik Ibrahim Malang - S Supriyono (IJISTECH (International Journal of Information System and Technology), 2021)
Rapidly evolving information systems and technology have compelled organizations, particularly educational institutions, to adapt their institutional evolution. The researcher's goal is to build an Odoo ERP-based institutional management system architecture at UIN Maulana Malik Ibrahim Malang in order to gain a competitive advantage in realizing the university's vision, mission, and goals, as well as in the future implementation phase of the recommended application portfolio. Information systems strategic planning is a significant transformation for a company, and it is based on user needs that are aligned with business strategy. The impact and alignment categories are used to categorize the information systems strategic planning technique. The impact category methodology is useful for creating and justifying the use of new information technologies. While the alignment methodology (alignment) serves to align the objectives of the information system with the goals of the organization. The Star UML was used to design the system architecture.